2022
DOI: 10.1002/hpm.3546
|View full text |Cite
|
Sign up to set email alerts
|

Old‐age dependency and catastrophic health expenditure: Evidence from Longitudinal Ageing Study in India

Abstract: Background Out‐of‐pocket (OOP) payments and catastrophic health expenditure (CHE) have a strong age gradient. Though studies have examined the socio‐demographic and geographic inequality in OOP payments and CHE in India, the role of old‐age dependency in financial catastrophe remains unclear. Disaggregated estimates of CHE by the level of old‐age dependency of households may help identify the most vulnerable sub‐group and provide evidence for specific policies for the financial protection and health care of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A study from Malawi and Nigeria concluded that the better off face higher CHE than people with low incomes [ 5 , 29 ]. On the other hand, studies from India and Bangladesh concluded that the poor face higher CHE than the rich [ 21 , 30 , 31 ]. Economic status highly dictates the care utilization pattern, but this variable also gave an assorted result.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from Malawi and Nigeria concluded that the better off face higher CHE than people with low incomes [ 5 , 29 ]. On the other hand, studies from India and Bangladesh concluded that the poor face higher CHE than the rich [ 21 , 30 , 31 ]. Economic status highly dictates the care utilization pattern, but this variable also gave an assorted result.…”
Section: Resultsmentioning
confidence: 99%
“…A study from Bangladesh also concluded that people from lower income quintiles have lower CHE as the utilization of formal care is low [ 31 ]. Conversely, poverty consistently predicts CHE, indicating that poor people have higher CHE [ 13 , 18 , 21 , 27 , 28 , 37 , 46 , 48 , 54 , 58 ]. To safeguard poor people from financial catastrophe, several studies from China, Kenya, and Malaysia emphasized on health insurance [ 19 , 20 , 36 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Similarly, from a study carried out in 42,949 households from Longitudinal Aging Study in India (LASI), it was concluded that households with high old-age dependency had a higher probability of incurring catastrophic health expenditure. 20 However all of these studies have used the health expenditure in excess to 40% of income after subsistence needs fulfilled as the criteria for catastrophic household expenditure. 10 In this study for 95% of the total elderly admissions the duration of hospital stay did not exceed 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…We take advantage of the recently released Longitudinal Study of Aging in India (LASI Wave 1, 2017Wave 1, -2018 to offer an empirical portrait of Third Agers in India. Considering that the aging scholarship in India has often articulated in the empirical language of dependency, care regimes, and (economic) insecurity (Bloom et al, 2010;Mohanty et al, 2022), we believe this examination allows us to shift the gerontological gaze from a risk perspective to one that is positive and affirmative. We do this by being fully aware of the cultural critique of responsibilization and purported autonomy of older citizens under neoliberal governance.…”
Section: Introductionmentioning
confidence: 99%